Beyond Profit Maximization: Reconstructing Conventional Strategic Management through the Perspective of Maqashid Shariah - Liya Setiawati; Muhardi Muhardi; Tasya Aspiranti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The dominance of the profit maximization paradigm has profoundly shaped strategic management by positioning competitive advantage, shareholder value, and financial performance as the primary indicators of organizational success. Although contemporary strategic approaches increasingly incorporate sustainability, stakeholder engagement, and Environmental, Social, and Governance (ESG) principles, these elements are generally treated as instruments for enhancing competitiveness rather than as the fundamental purpose of organizational strategy. This conceptual study aims to reconstruct conventional strategic management through the philosophical perspective of Maqashid Shariah, repositioning maslahah as the overarching objective of strategic decision-making. The study adopts a qualitative conceptual research design based on critical literature analysis and theory synthesis, integrating established strategic management theories with the principles of Maqashid Shariah. The analysis demonstrates that strategic management requires a paradigm shift from profit maximization toward holistic value creation encompassing economic prosperity, ethical governance, stakeholder welfare, environmental stewardship, and spiritual accountability. Based on this synthesis, the study proposes the Maqashid Strategic Management Framework (MSMF), which integrates five strategic dimensions into a coherent framework for sustainable organizational excellence. Furthermore, the study introduces Maslahah Advantage as a novel higher-order strategic construct that extends the traditional concept of competitive advantage by emphasizing multidimensional value creation aligned with the objectives of Maqashid Shariah. The proposed framework contributes to strategic management theory by providing an alternative philosophical foundation for evaluating organizational success while offering practical guidance for organizations seeking ethical, sustainable, and human-centered strategic development.